2017
DOI: 10.1007/s10877-017-0076-1
|View full text |Cite
|
Sign up to set email alerts
|

Video-based heart rate monitoring across a range of skin pigmentations during an acute hypoxic challenge

Abstract: The robust monitoring of heart rate from the video-photoplethysmogram (video-PPG) during challenging conditions requires new analysis techniques. The work reported here extends current research in this area by applying a motion tolerant algorithm to extract high quality video-PPGs from a cohort of subjects undergoing marked heart rate changes during a hypoxic challenge, and exhibiting a full range of skin pigmentation types. High uptimes in reported video-based heart rate (HRvid) were targeted, while retaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…However, the authors also mentioned that the lack of environmental control leads to increased humidity and possibly increased vasodilation [ 41 ]. In addition to these examples, numerous other studies that stratify results against Fitzpatrick classification identify the same trend; errors in determining heartrate from wearable PPG devices that use primarily green light as their source is increased in individuals with dark skin tones due to the high absorption caused by increased amounts of epidermal melanin [ 42 , 43 , 44 , 45 ]. Lastly, Bent et al published an experimental analysis of error observed in optical heart rate sensors manufactured by Apple (Apple Watch 4), Fitbit (Fitbit Charge 2), Garmin (Garmin Vivosmart 3), Xiaomi (Xiaomi Miband 3), Empatica (Empatica E4), and Biovotion (Biovation Everion) as a function of skin tone [ 46 ].…”
Section: Individual Variations In the Human Populationmentioning
confidence: 90%
“…However, the authors also mentioned that the lack of environmental control leads to increased humidity and possibly increased vasodilation [ 41 ]. In addition to these examples, numerous other studies that stratify results against Fitzpatrick classification identify the same trend; errors in determining heartrate from wearable PPG devices that use primarily green light as their source is increased in individuals with dark skin tones due to the high absorption caused by increased amounts of epidermal melanin [ 42 , 43 , 44 , 45 ]. Lastly, Bent et al published an experimental analysis of error observed in optical heart rate sensors manufactured by Apple (Apple Watch 4), Fitbit (Fitbit Charge 2), Garmin (Garmin Vivosmart 3), Xiaomi (Xiaomi Miband 3), Empatica (Empatica E4), and Biovotion (Biovation Everion) as a function of skin tone [ 46 ].…”
Section: Individual Variations In the Human Populationmentioning
confidence: 90%
“…A couple of works considered the impact of skin pigmentation [51][52][53][54]. Those works show the tendency of higher values in the Fitzpatrick scale to degrade the results but proper methods might be able to compensate for the skin tone.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most obvious appearance characteristic when measuring the blood volume pulse optically is skin type. Previous work has found systematic biases in the performance of non-contact photoplethymography measurement algorithms with skin type [40], [22]. Specifically, performance is over signficantly poorer for darker skin types.…”
Section: Diversity Of Subjects In the Training Setmentioning
confidence: 99%